STRATEGI PENGEMBANGAN USAHATANI KOPI ARABIKA (Coffea arabica) DI DESA PAGUR KECAMATAN PANYABUNGAN TIMUR KABUPATEN MANDAILING NATAL SUMATERA UTARA - Yuli Paisah ,; Fiddini Alham ,; Thursina Mahyuddin , (Jurnal Cakrawala Ilmiah, 2024)
Mandailing Natal Regency is one of the coffee-producing areas in North Sumatra Province. The largest community coffee plantation in Mandailing Natal Regency belongs to Pagur Village, which is located in East Panyabungan District. This research was conducted with the aim of identifying and analyzing internal factors (strengths and weaknesses) and external factors (opportunities and threats) of arabica coffee farming in Pagur Village, Panyabungan Timur District and to analyze the right strategy to be implemented in developing coffee farming in Pagur Village. The survey method is the method chosen in carrying out this research. A total of 39 people from Pagur Village were chosen to be respondents or samples in the study. The analysis used in this study is descriptive analysis using SWOT analysis, Position Matrix and SWOT Matrix, to formulate "Arabica Coffee (Coffea arabica) Farming Development Strategy in Pagur Village, Panyabungan Timur District, Mandailing Natal Regency, North Sumatra", so that the results obtained are that alternative strategies that can be utilized in this research, namely by maximizing the use of coffee land owned by arabica coffee farmers in Pagur Village, repairing roads or access to Arabica coffee farming locations to make it easier for farmers to go to their business locations, as well as facilitating and minimizing the distribution costs of Arabica coffee. , maximizing the use of existing technology to obtain a higher selling price of coffee